Experiencing time in Estonian constructions with an adjective and an MA-infinitive - Hebedová, Petra (Baltistica, 2020)
In this article I present the characteristics of the Estonian construction combining an adjective and an MA-infinitive in illative (X is ADJ V-MAINF), such as in Lili oli kärme plaksutama ‘Lili was quick to applaudʼ or robot on võimeline ülesandeid lahendama ‘the robot is able to carry out tasksʼ. In this construction the subject is characterised by means of a copula and an adjective, and this characterisation is related to an activity that is specified by a verb in the MA-infinitive form. Using corpus data I provide an overview of the types of subjects that appear in the construction. Is the subject usually human? Can it be inanimate? How does the character of the subject affect the meaning of the sentence? Next I concentrate on a specific subvariant of the construction that takes an inanimate subject, such as in Sügis on kiire tulema ‘Autumn is quick to come’ or Petlik mulje on kerge tekkima ‘A false impression is easily formed’ (lit. a false impression is easy to come into existence), in which the meaning of the sentence is related to the experience of time and includes a prediction of how likely or unlikely an event is to occur or be experienced. The article presents a description of this specific variant and its meaning based on corpus examples and argues that this category of sentences should be treated as a subschema of X is ADJ V-MAINF because it has features that are not found in the general construction. The article uses the framework of cognitive grammar (Langacker 1987; 2000; 2008) and in particular the term constructional schema (Langacker 2000, 21, 32–33; 2008, 23–24, 168).